Exposure to polycyclic aromatic hydrocarbons and genotoxic effects on nonsmoking Swedish road pavement workers - Järvholm, Bengt; Nordström, G; Högstedt, Benkt; Levin, Jan-Olof; Wahlström, Jan; Östman, C; Bergendahl, C (Scandinavian Journal of Work, Environment & Health, 1999)
' ' OBJECTIVES ': 'The objective of this study was to investigate exposure to polycyclic aromatic hydrocarbons (PAH) from asphalt fumes among Swedish road pavement workers and determine whether any effects could be detected with genotoxic tests.' ' METHODS ': 'The study included 28 nonsmoking road pavers and 30 nonsmoking referents. The concentration of PAH was determined in the breathing zone of the road pavers. 1-Hydroxypyrene was analyzed before and after shifts of asphalt work and during the afternoon for referents. Sister chromatid exchanges (SCE) and micronuclei (MN) were determined in peripheral lymphocytes.' ' RESULTS ': 'Several 3- or 4-ring PAH were found, and the analysis indicated that they occurred in bitumen fumes rather than in traffic fumes. The average total concentration of PAH was 2.3 (range 0.2-23.8) mg/m3. The concentration of 1-hydroxypyrene in urine was higher for the road pavers than for the referents, but there was no significant difference between the pre- and postshift values of the road pavers. The road pavers had no significant increase in SCE or MN.' ' CONCLUSION ': 'The study showed that Swedish road pavers have an increased exposure to PAH from bitumen fumes, but no genotoxic effects could be detected by SCE or MN tests.
Keywords: asphalt; bitumen; epidemiology; micronucleus; occupation; sister chromatid exchange